2010
DOI: 10.1038/ncb2125
|View full text |Cite
|
Sign up to set email alerts
|

The orphan nuclear receptor Nurr1 restricts the proliferation of haematopoietic stem cells

Abstract: Successful hematopoiesis requires long-term retention of the quiescent state of hematopoietic stem cells (HSCs). The transcriptional regulation of stem cell quiescence, especially by factors with specific functions in HSCs, is only beginning to be understood. Here we demonstrate that Nurr1, a nuclear receptor transcription factor, has such a regulatory role. Enforced expression of Nurr1 drives early hematopoietic progenitors into quiescence. When stem cells overexpressing Nurr1 are transplanted into lethally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 43 publications
1
77
1
Order By: Relevance
“…Jian Wang 1 , Jing Yang 2 , Ying Zou 1 , Guo-Liang Huang 1 , Zhi-Wei He 1 * Sirin et al, 2010), apoptosis (Ke et al, 2004), migration (Maijenburg et al, 2012) and differentiation in a cell type-specific manner. Recently, the oncogenic activities of Nurr1 are emerging.…”
Section: Orphan Nuclear Receptor Nurr1 As a Potential Novel Marker Fomentioning
confidence: 99%
“…Jian Wang 1 , Jing Yang 2 , Ying Zou 1 , Guo-Liang Huang 1 , Zhi-Wei He 1 * Sirin et al, 2010), apoptosis (Ke et al, 2004), migration (Maijenburg et al, 2012) and differentiation in a cell type-specific manner. Recently, the oncogenic activities of Nurr1 are emerging.…”
Section: Orphan Nuclear Receptor Nurr1 As a Potential Novel Marker Fomentioning
confidence: 99%
“…Received May 10, 2011;revised version accepted August 31, 2011. Nur77 (NR4A1), Nurr1 (NR4A2), and Nor1 (NR4A3) are orphan members of the nuclear receptor family that have been suggested to function as ligand-independent transcription factors (Baker et al 2003;Wang et al 2003). A distinguishing feature of the NR4A family of nuclear receptors is that they are rapidly induced by various acute stimuli and are functioning in adaptive and stress-responsive physiological functions, in addition to important roles in cellular differentiation into midbrain dopamine neurons and cells of the hematopoietic lineage (Zetterströ m et al 1997;Castillo et al 1998;Saucedo-Cardenas et al 1998;Ponnio et al 2002;Mullican et al 2007;Pearen and Muscat 2010;Sirin et al 2010;Zhao and Bruemmer 2010). Moreover, NR4A proteins have recently been identified as tumor suppressors in myeloid cells, and NR4A loss of function results in acute myeloid leukemia (Mullican et al 2007;Ramirez-Herrick et al 2011).…”
mentioning
confidence: 99%
“…On the other hand, loss of one Nurr1 allele resulted in enhanced cycling and sensitivity to the chemotherapeutic agent 5-fluorouracil (5-FU). Molecular analysis showed that Nurr1 overexpression is positively correlated with the upregulation of the cell-cycle inhibitor p18 INK4C , suggesting a mechanism by which Nurr1 may regulate HSC quiescence (Sirin et al, 2010).…”
Section: Nurr1mentioning
confidence: 99%
“…The results of in vitro overexpression and knockdown experiments identified a role for necdin in the maintenance of HSC quiescence and self-renewal. However, necdin appears to have a modest functional role in HSCs in vivo (Kubota et al, 2009), and necdin overexpression does not result in enhanced HSC quiescence (Sirin et al, 2010).…”
Section: P53mentioning
confidence: 99%